A Practical Proposal to End Corporate Tax Abuse: METR, a Minimum Effective Tax Rate for Multinationals - Alex Cobham; Tommaso Faccio; Javier Garcia-Bernardo; Petr Jansky; Jeffery Kadet; Sol Picciotto (Charles University in Prague, Institute of Economic Studies (IES), 2021)
An initiative is needed to break the logjam in the international negotiations to reform taxation of multinational enterprises (MNEs). The explosion of profit shifting observed since the 1990s has resulted in hundreds of billions of dollars of tax revenues being lost around the world each year - but reform efforts have thus far failed to deliver measurable progress on the primary agreed goal of better aligning MNEs' taxable profits with the location of their real economic activity. More recently, countries have committed also to ensure that MNEs' global profits are subject to a minimum effective tax rate, but progress towards international agreement remains stalled. Our proposal for a minimum effective tax rate (METR) could be applied to MNEs by any countries that choose to do so, whether they are home to MNEs, host of MNEs, or both. The METR would be compatible with existing tax treaties, but being non-discriminatory it also complies with other international obligations and could be introduced unilaterally. Economic modelling shows the METR would deliver major revenue gains for participating countries, and adoption would also contribute to, rather than impede, momentum for a more comprehensive multilateral agreement.
Keywords: F23; H25; H32; 330; multinational enterprise; corporate taxation; tax reform; effective tax rate; minimum tax; minimum effective tax rate; Unternehmensbesteuerung; Körperschaftsteuer; Steuertarif; Steuerreform; Multinationales Unternehmen; Welt